E-Procurement in the Procurement System for Goods/Services by the Government in Indonesia: Perspective of Saddu al-Dhariah - Kusumadewi, Mutiara Ramadhani; Aseri, Akh. Fauzi; Seff, Syaugi Mubarak (Universitas Islam Sultan Agung, 2022)
This research is motivated by the release of Presidential Regulation No. 16 of 2018 concerning the Procurement of Goods/Services, which has three important stages: preparation, selection, and implementation. The issuance of this presidential rule aims to enhance the utilization of products from local Micro, Small, and Medium Enterprises (MSMEs). In the age of digitization, the Indonesian government has developed an electronic-based system known as e-procurement for the acquisition of products and services. This enhances the efficiency, effectiveness, competitiveness, transparency, fairness, accountability, and integrity of the procurement process, while also ensuring it is free from corrupt practices. This study aims to examine the e-procurement system in Indonesia through the lens of the fiqh principle of saddu al-dhariah, with the goal of mitigating corrupt practices in the procurement of products and services. The main data in this study revolves around Presidential Regulation No. 16 of 2018. Secondary data is derived from multiple sources including case studies on the procurement of goods and services, as well as publications and reports published by the Government Goods/Services Procurement Policy Institute (LKPP). The study findings suggest that e-procurement adheres to the principle of saddu al-dhariah by effectively mitigating state losses and enhancing government operational efficiency. The general public reaps advantages from this approach as it leads to a surge in the sales of domestic MSME products. Nevertheless, LKPP must persist in monitoring this mechanism to prevent any discussions conducted by parties with personal or collective interests.